Associations between sleep problems and emotional/behavioural difficulties in healthy children and adolescents - Theresa Fulfs; Tanja Poulain; Mandy Vogel; Kolja Nenoff; Wieland Kiess (BMC, 2024)
Abstract Objective This study aimed to (1) characterise sleep disturbances and emotional/behavioural difficulties among healthy German children and adolescents aged 3 to 13 years, (2) examine the association between parent-reported sleep problems and emotional/behavioural difficulties, (3) point out possible relations between specific kinds of sleep disturbances and different behavioural difficulties. Methods Data were collected between 2011 and 2015 within the LIFE Child study in Germany. The sample included 1101 3- to 13-year-old children and adolescents. Information on sleep disturbances-assessed via the Children's Sleep Habits Questionnaire (CSHQ), emotional/behavioural difficulties-assessed via the Strengths and Difficulties Questionnaire (SDQ), and socioeconomic status was provided by participants' parents. Multiple regressions were applied to analyse the associations between general and specific sleep disturbances (independent variables) and emotional/behavioural difficulties (dependent variables). Results The total CSHQ score was positively associated with the total SDQ score and all SDQ subscales (emotional problems, conduct problems, hyperactivity/inattention, peer relationship problems). Most of the CSHQ subscales were related to SDQ subscale scores, except for a few non-significant relations with hyperactivity/inattention and conduct problems. The CSHQ total score, daytime sleepiness, sleep duration and parasomnias showed the strongest associations with the SDQ total score. Conclusion This study confirms an association between children's and adolescents' sleep habits and psychological health. We were able to demonstrate the association between sleep problems and emotional/behavioural difficulties in a large sample of healthy participants. In particular, we observed a significant relation between parasomnias and hyperactive/inattentive behaviour as well as a significant association between emotional problems and sleep problems, especially daytime sleepiness, sleep anxiety and parasomnias.